CERT System and Network Security Practices - SINGH, YASHWANT KUMAR; RATAWA, SURYA PRAKASH (IJRDO -Journal of Computer Science Engineering, 2017)
Networks have become indispensable for conducting business in government,commercial, and academic organizations. Networked systems allow you to access needed information rapidly, improve communications while reducing their cost, collaborate with partners, provide better customer services, and conduct electronic commerce. While computer networks revolutionize the way you do business, the risks they introduce can be fatal to a business. Attacks on networks can lead to lost money, time, products, reputation, sensitive information, and even lives. Systems, networks, and sensitive information can be compromised by malicious and inadvertent actions despite an administrator’s best efforts. Even when an administrator knows what to do, they often don’t have the time to do it; operational day-to-day concerns and keeping systems functioning take priority over securing those systems. The knowledge that most system and network administrators have about protecting and securing systems typically comes from experience and word-of-mouth, not by consulting a published set of procedures that serve in the role of de facto standards generally accepted by the administrator community; these do not currently exist. For this reason and others described in this paper, an administrator needs easy-to-access, easy-tounderstand, easy-to-implement security practices. The CERT system and network security practices are intended to meet these needs. CERT security practices are organized into five top-level steps: Harden/Secure, Prepare, Detect, Respond, and Improve. A total of fifty current practices comprise these steps. They are summarized in this paper and fully documented on the CERT web site at http://www.cert.org. The practices to harden and secure systems form a strong foundation by establishing secure configurations of computing assets. Prepare, Detect, Respond, and Improve practices assumes that Harden/Secure practices have been implemented and provide further guidance on what to do when something suspicious, unexpected, or unusual occurs.